Nuclear protein p68 is an RNA-dependent ATPase. - Iggo, R D (1989)
The human nuclear antigen p68 cross reacts with a monoclonal antibody to SV40 large-T antigen. Its deduced amino acid sequence contains short motifs which place it in a large superfamily of proteins of known or putative helicase activity. Recently, a p68 subfamily (DEAD box proteins) which share more extensive regions of homology has been identified in mouse, Drosophila, Saccharomyces cerevisiae and Escherichia coli. These proteins are involved in translation, ribosome assembly, mitochondrial splicing, spermatogenesis and embryogenesis. We show here that immunopurified human p68 has RNA dependent ATPase activity. In addition, we show that the protein undergoes dramatic changes in cellular location during the cell cycle.